Modeling of the solidarity banking system in Congo: towards human development based on traditional African values - BOUNDJA, Claver (Advances in Social Sciences Research Journal, 2021)
Among the institutional instruments likely to participate in the economic development of a country, banks occupy a crucial place, as their role affects means of payment, exchanges, credit, financial transactions and advice. The analysis of paradigms and mechanisms of the banking system makes it possible to intervene in the heart of the economic system. Congo’s banking system, like that of almost all African countries, is characterized by half a century of failure, several bankruptcies, endemic corruption, the embezzlement and exclusion of so-called poor populations and rural. This article proposes a model of the endogenous financing of the real economy through solidarity banks. Our objective is to formulate a decision-making tool for economic and financial governance, in terms of financing local development. We propose to explain the importance of monetary policy and the renovated banking system on endogenous bases, according to traditional African values.